PENGARUH VARIAN MENU, STORE ATMOSHPHERE DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA HISANA FRIED CHIKEN - Nasution, Muhammad Ali Makmur; Lubis, Adelina (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The purpose of this research is to find out the influence of menu variants on purchasing decisions, to find out the influence of menu variants on purchasing decisions, to find out the influence of digital marketing on purchasing decisions and to find out the influence of menu variants, store atmosphere and digital marketing on Fried purchasing decisions at Hisana Chicken. The population in this study was 100 people who purchased Hisana Fried Chicken Jl Karya, Gg Sehati No. 12. The sample in the research was 100 people obtained using saturated samples. The data collection technique used in this research was carried out by distributing questionnaires. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination. The research results show that menu variants have a positive and significant influence on purchasing decisions, store atmosphere has a positive and significant influence on purchasing decisions, digital marketing has a positive and significant influence on purchasing decisions and menu variants, store atmosphere and digital marketing simultaneously influence Fried purchasing decisions at Hisana Chiken.